A transudative chylothorax associated with superior vena cava syndrome. (2019) - Austin, Adam; Al-Faris, Faris; Modi, Aakash; Chopra, Amit
Abstract: The chylothorax is a lymphocyte predominant protein-discordant exudative pleural effusions with low lactate dehydrogenase and elevated triglyceride levels. Transudative chylothoraces associated with Superior Cava syndrome (SVC) are an extremely rare clinical entity. In this manuscript, we describe a case of transudative chylothorax due to SVC obstruction secondary to thrombosis of a peripheral inserted central venous catheter, which ultimately resolved after endovascular intervention. In our review of the literature, only five cases of transudative chylothorax associated with SVC syndrome were identified with 60% of cases associated with thrombosis and complications due to catheters in the central venous circulation. Treatment of the underlying cause is key to resolution of the chylothorax. Thoracentesis is an initial intervention for diagnostic and therapeutic purposes. Endovascular intervention is the primary mode of treatment for SVC thrombosis and stenting is preferred for malignant causes, however anticoagulation alone has been reported in the resolution of chylothorax. In patients with recurrent chylothorax despite of relief of SVC obstruction, a medium-chain triglyceride diet and octreotide can be prescribed in order to decrease the chyle flow in the thoracic duct. Surgical ligation of the thoracic duct can be considered if medical management and endovascular treatment fails.